Anatomical changes induced by selection for plant architecture in maize (Zea mays L.) - Môro, F. V. [UNESP]; Môro, J. R. [UNESP]; Damião Filho, C. F. [UNESP]; Taveira, L. R. [UNESP] (My University, 1998)
The original brachytic population 'Dent Single Cross Composite' (DSCC-br2br2) and a selection-derived sub-population with modified plant architecture (DSCC-br2br2-Lg3Lg3, selected for erect leaves), were evaluated for the following characteristics number of vascular bundles of greater and smaller size, total vascular tissue area (phloem and xylem), sustaining tissue area (vascular tissue plus sclerenchyma), phloem and sclerenchyma areas in apical, medial and basal portions from midclub and in apical and basal sheath regions (from second leaf above and first below ear insertion). These variables had different values for the five different sections studied in each leaf and these differences did not have the same pattern in the two DSCC populations (brachytic and with modified architecture). Selection for architectural modification caused some indirect foliar anatomical modifications. With the exception of the phloem and the vascular tissue areas in apical leaf and sheath base regions, the modified plant architecture population showed smaller values of sustaining tissue area, sclerenchyma area, vascular tissue area and number of smaller vascular bundles than the original one. In the ligule region the modified maize leaves had smaller vascular and sustaining tissue areas, reducing transportation area, which could reduce gram yield.
Keywords: Anatomy; Corn; Leaf angle; anatomy; phloem; xylem